Stock Market Trading between Legal Formalities and Economic Substance: A Macro-Sharia Appraisal - Abozaid, Abdulazeem; Elamrawy, Sama; Abdullah, Fuady (Justicia Islamica, 2026)
This study examines stock market trading from a macro-sharia perspective by grounding normative evaluation in the empirical realities of contemporary financial markets. Using descriptive empirical analysis of selected stock market indices from developed and emerging economies over the period 2005–2025, the paper explores patterns of price volatility and market behavior that characterize modern stock market trading practices. The findings indicate that persistent volatility, sharp price fluctuations, and speculative dynamics often weaken the linkage between market prices and underlying economic fundamentals, particularly in emerging markets. Building on these empirical observations, the study reassesses stock market trading in light of Shariah principles and the broader objectives of Islamic law (maqāṣid al-sharīa), emphasizing the importance of incorporating systemic outcomes and real economic effects into Shariah evaluation. The paper contributes to the Islamic finance literature by highlighting the need to move beyond purely formal assessments toward a more context-sensitive, macro-level approach.